Human Immunodeficiency Virus Infection and Pregnancy - Schwarz, Richard H. (Hindawi Publishing Corporation, 1994)
The human immunodeficiency virus (HIV) epidemic is clearly one of the most serious health-care crises in the professional lives of contemporary physicians. It cannot be regarded as a curiosity to be dealt with by inner-city infectious-disease experts, but rather must be considered a problem for all health-care providers and a problem in which the obstetrician-gynecologist has a special role to play.